PHARMACOCOSMETOLOGICAL APPROACH TO ACNE TREATMENT: COSMECEUTICALS AND DERMATOLOGICAL DRUGS - Naguliak, Halyna (Global Prosperity, 2026)
The aim. To develop a methodology and step-by-step algorithm for acne treatment for specialists. The study aims to create an effective approach that helps physicians select optimal therapeutic strategies for patients with various forms of acne. Materials and Methods. A review of scientific literature and clinical guidelines on acne treatment was conducted. The study examined the pathogenetic mechanisms of the disease, key therapeutic strategies, and combined treatment methods. Special attention was given to the use of retinoids, benzoyl peroxide, antibiotics, and cosmeceutical products. Results. The analysis revealed that combining traditional dermatological drugs with cosmeceuticals enhances the skin’s barrier function, reduces inflammation, and regulates sebum production. Clinical cases demonstrated the effectiveness of this approach. Additionally, chemical peels, proper cleansing, and skin hydration were found to contribute to long-term remission. Conclusions. The article highlights the necessity of a comprehensive approach to acne therapy. It was determined that the combination of pharmacological treatment and cosmeceuticals not only facilitates rapid symptom relief but also ensures a long-lasting effect and improves patients’ quality of life. A personalized approach to therapy, depending on the type and severity of acne, is recommended.